(untitled) (Tidsskrift for Praktisk Teologi, 2023)
The presence of migrants in precarious life situations with limited welfare rights challenges the Nordic national churches to reconsider their role vis-à-vis the welfare state. The aim of this article is to discuss what such a reorientation should imply. Through an engagement with the works of William T. Cavanaugh, Gustaf Wingren, and Gyrid Gunnes, I argue for a church of diaconia that takes the situation of migrants with limited welfare rights into account by being a space of recapitulation and justice, while at the same time keeping the welfare state accountable to its responsibility of protecting vulnerable lives.